Colonial religion: conflict and change in church and state - Kaye, Bruce (ATF Press, 2020)
Half-title Page -- Title Page -- Copyright -- Table of Contents -- Author Information -- Acknowledgments -- Sources -- Introduction -- 1. The 'Old High Church' Baggage of William Grant Broughton -- 2. Laity in Church Governance-Broughton's Non-Adventure -- 3. The Collapse of the Royal Supremacy: Broughton's Struggle -- 4. Broughton's 1850 Bishops Conference and the Energetic Bishop Selwyn -- 5. The Strange Birth of Anglican Synods in Australia and the 1850 Bishops Conference -- 6. Church Conflict and the Founding of Sydney University -- 7. From Anglican Gaol to religious Plurality: How Time has Changed the Terms of Reference in 'Church State Relations' -- Index of Names and Subjects.